(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
Studies have shown that, people suffer from the effects of climate change. The consequences of natural disasters include shock reactions, post-traumatic stress disorder (PTSD), depression, anxiety, phobic disordersand suicidal behavior. In addition to poor harvests and economic losses, changes in the natural environment cause a grief and sorrow due to the loss of important places and landscapes.Every human being is affected by the consequences of climate change, especially since climate change is at a stage when a “red code” for humanity is included. Some categories of people are more vulnerable to the potential impacts of climate change. They are: children, elderly, chronically ill, people with cognitive impairments, limited mobility, pregnant women, people with mental health disorders, with lower socioeconomic status, migrants, refugees, the homeless.In Macedonia in 2021 a survey was conducted on the impact of the effects of climate change on mental health. Data showed that although most respondents know what climate change is and consider it a moderate risk in society, almost all respondents said that they cause some of the negative emotions such as depression, despair, hopelessness, fear and powerlessness. Most of the respondents either do not know what the relevant Macedonian institutions are doing to prevent and mitigate the consequences of climate change or they think that the Macedonian society is not taking measures in that direction.Given the importance of preventing the mental health of the population, we hope that the findings of this research would be useful in creating state policies and strategies for tackling climate change.